Assessment of NB-UVB Effects on Skin of Atopic Dermatitis Patients: A Network Analysis: Assessment of NB-UVB effects on skin of atopic dermatitis patients - Rezaei-Tavirani, Mostafa; Bandarian, Fatemeh; Razi, Farideh; Razzaghi, Zahra; Arjmand, Babak; Rostami Nejad, Mohammad (Journal of Lasers in Medical Sciences, 2024)
Introduction: Atopic dermatitis is a common inflammatory skin disease which is treated with narrowband ultraviolet B (NB-UVB). Exploring the critical targeted genes in patients by UV radiation is the main aim of this study. Methods: Gene expression profiles of lesional and non-lesional skin samples of atopic dermatitis patients after treatment with NB-UVB and the non-irradiated samples were extracted from the Gene Expression Omnibus (GEO) database and analyzed via protein-protein interaction (PPI) network analysis to find the critical targeted genes. Results: A total of 357 significant differentially expressed genes (DEGs) were included in the PPI network. CTNNB1, SRSF1, YWHAB, SMC3, GNB2, ARF3, UBL7, RAB2A, YWHAE, EIF5B, SNRPE, PPIG, RC3H2, CFL1, SMARCB1. LAPTM5, PRPF40A, and RBBP4 were introduced as hub bottlenecks. Conclusion: In conclusion, five central genes including SMC3, ARF3, EIF5B, SMARCB1, and LAPTM5 were highlighted as critical genes in response to NB-UVB radiation in the skin of the treated atopic dermatitis patients. The introduced crucial genes are involved in essential cellular functions such as apoptosis, cell cycle, cell proliferation, and inflammation. It seems that applied NB-UVB radiation is a suitable therapeutic method for atopic dermatitis disease.